POP-UP SEBAGAI MEDIA PEMBELAJARAN FISIKA MATERI ALAT-ALAT OPTIK UNTUK SISWA SEKOLAH MENENGAH ATAS (UPEJ Unnes Physics Education Journal, 2017)
Physical learning of optical instruments subject in the SMA N 13 Semarang used media such as power point, books, video, and internet. Teacher had not developed yet another innovative learning media. The research’s purpose was for knowing the appropriateness media developed into Pop-Up Book form of optical instruments subject. The appropriateness media was tested use questionnaire, documentation, and test methods to know effectiveness level of Pop-Up Book. The samples of this research were students of grade X, physical teacher, media expert, and also subject expert. The Pop-Up Book which was resulted have effectiveness level was 75.42%, which was include into very good criteria. The appropriateness average score of Pop-Up Book was 80.62% which was include into good criteria. Based on the indicator had been established and the result of data respondent, so Pop-Up Book worth used as physical learning media of optical instruments for senior high school students.